Coronavirus outbreak in Italy: Physiological benefits of home-based exercise during pandemic - Ravalli, S.; Musumeci, G. (Journal of Functional Morphology and Kinesiology, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic has forced the hardest-hit populations, like Italians, to radically change their daily habits, starting with social distancing, strict preventive measures, and self-isolation. These precautions also apply to sport-related facilities and activities. The difficulty to practice physical activity during this dramatic moment in time adds to the risks associated with sedentary habits, due to staying all the time at home. Here, the importance and the benefits of maintaining exercise routine, even at home, are emphasized in order to avoid the consequences of inactivity.